Finite-element analysis to predict residual stress and strain in press-braked cold-formed steel section - Mutafi, Ayad Abdullah Mohammaed (2020)
Cold formed steel sections are normally produced by cold work manufacturing processes. The amount of cold work to form the sections induces residual stresses and strains in the sections, especially in the forming zone and that due to these effects the load carrying capability of the structural members can be significantly reduced. In design, the longitudinal residual strain has been an important indicator to determine the geometric behaviour of the formed section. Over the years, many attempts have been made to investigate the residual stress/strain behaviour: analytical, laboratory measurements and numerical predictions. Numerical method has been recommended by researchers as the appropriate method to overcome the analytical limitation and laboratory work drawback (e.g. tedious calculation in complex sections and material wastage).